Molecular characterization of hepatitis B virus in blood donors from Burkina Faso: Prevalence of quasi‐subgenotype A3, genotype E, and mixed infections. Issue 12 (14th June 2016) - Candotti, Daniel; Diarra, Birama; Bisseye, Cyrille; Tao, Issoufou; Pham Quang, Kei; Sanou, Mahamoudou; Laperche, Syria; Sanogo, Rokia; Allain, Jean‐Pierre; Simpore, Jacques
Abstract : Burkina Faso is a highly endemic area for Hepatitis B virus (HBV) which remains a major challenge for blood safety with >13% of candidate blood donors being chronically infected. However, little is known about the molecular epidemiology of the viral strains currently circulating. In this study, 99 HBV strains from HBsAg positive candidate blood donors in Ougadougou were genetically characterized by sequencing the pre‐S/S region of the viral genome. Phylogenetic analyses revealed a 25% prevalence of HBV quasi‐subgenotype A3 (A3QS ) co‐circulating with the confirmed dominant HBV genotype E (72%). HBV/A3QS sequences formed a sub‐cluster closely related to West‐African sequences previously characterized, and showed a low intra‐group genetic diversity (0.75%) suggesting a relatively recent spreading of HBV/A3QS strains in Burkina Faso. Low genetic diversity of genotype E strains compared to A3QS was confirmed. Mixed infections with the two genotypes were identified in 3% of the donors tested and contributed to artifacts during PCR amplification of the viral genome leading to erroneous apparent intergenotype recombinant sequences. While the co‐circulation of two HBV genotypes in a restricted area may favor the emergence of intergenotype recombinant variants, strictly controlled molecular experimental procedures should be used to accurately characterize HBV circulating recombinant forms. J. Med. Virol. 88:2145–2156, 2016 . © 2016 Wiley Periodicals, Inc.